PENGARUH PERUBAHAN HIPERPLASIA SEL GOBLET SELAMA 28 HARI PAPARAN ASAP ROKOK DENGAN PEMBERIAN ANTIOKSIDAN SUPEROXIDE DISMUTASE - Rivan Virlando Suryadinata; Bambang Wirjatmadi; Merryana Adriani (Universitas Airlangga, 2016)
The number of Indonesian smokers in 2013 has reached 36.3% and continues to increase each year. This will directly affect the increase in passive smokers in Indonesia. Harmful free radicals from cigarette smoke inhaled can lead to irritation of the bronchial airways. Irritation of the airways characterized by mucus hypersecretion induced goblet cell hyperplasia of the bronchi. Giving antioxidants superoxide dismutase melon extract with a combination of gliadin (SOD-gliadin) reduces radical that goblet cell hyperplasia in the bronchial airways can be reduced. This study aims to determine the effectiveness of the SOD-gliadin to the decrease of goblet cell hyperplasia of the bronchi. Giving SOD-gliadin carried out for 28 days with exposure to smoke two cigarettes per day using 5 groups: negative control, positive control and 3 treatment groups with different doses (2,25 IU; 4,5 IU; 9 IU). Observation of goblet cell hyperplasia performed on histological preparations with a longitudinal section with four visual field. With the effects of the antioxidant superoxide dismutase melon extract on percentage of goblet cell hyperplasia (ANOVA, p = 0396). It can be concluded supplementation with SOD-gliadin not influence the percentage of goblet cell hyperplasia.Keywords: goblet cell, superoxide dismutase, antioxidants, cigarette, free radical